A novel and controllable method for simultaneous preparation of human milk fat substitutes (OPL, OPO and LPL): two-step enzymatic ethanolysis-esterification strategy. (January 2023) - Li, Yali; Zhang, Yi; Zhou, Yibin; Zhang, Yufei; Zheng, Mingming
Graphical abstract: Highlights: This is the first investigation into the controllable preparation of OPL, OPO and LPL. CSL@OMS-C8 showed better specific activity and reusability than lipase CSL. The ethanolysis-esterification strategy inhibited acyl migration. The HPLC-ELSD and UPLC-TOF-MS/MS techniques were coupled to be effective for the discrimination of TAGs molecular species. Abstract: A novel and effective approach based on the two-step ethanolysis-esterification strategy was proposed for the controllable and simultaneous preparation of 1-oleoyl-2-palmitoyl-3-linoleoylglycerol (OPL), 1, 3-dioleoyl-2-palmitoyl-glycerol (OPO) and 1, 3-dilinoleoyl-2-palmitoyl-glycerol (LPL) with adjustable proportions. Enzymatic ethanolysis of fractionated palm stearin was carried out to yield 2-monopalmitoylglycerol (79.4 ± 0.6 %) with over 91.0 % purity at the optimal conditions. The immobilized Candida sp. lipase (CSL) on octyl-functionalized ordered mesoporous silica (OMS-C8 ) was applied to re-esterify 2-monopalmitoylglycerol with oleic acid and linoleic acid for the simultaneous production of OPL, OPO, and LPL. The total content in the final products was 81.5 %, with 91.3 % of palmitic acid (PA) content at the sn -2 position. Besides, OPL/OPO/LPL was conveniently prepared with suitable proportions for worldwide infants by adjusting the ratio of acyl donors. This paper provides a novel and effective two-step ethanolysis-esterification strategy for the development of human milk fat substitutes (HMFS).